PENGARUH TEORI BELAJAR SKINNER MELALUI MODEL PICTURE AND PICTURE TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS - Hendar Ahmad Wibisono; Hendri Eka Jaya Putra; Suyitno Muslim (Akademika, 2021)
The purpose of this research is to find out the improvement of students' mathematical understanding skills whose learning uses Skinner's learning theory through the Picture and Picture model. The research method used is a true experimental method with a purposive sample of class VIII SMPIT Ibnu Hajar Mandiri Bekasi for the 2020/2021 academic year, amounting to 36 students. Sampling was done purposively with SPSS 26. The instruments are in the form of test questions describing students' mathematical understanding abilities on function material and questionnaire sheets. The results showed that learning mathematics using Skinner's learning theory through Picture and Picture models can increase students' mathematical understanding skills by 81% with very good interpretation, besides that there are differences in the mathematical understanding of students whose learning uses Skinner's learning theory through Picture and Picture models with students who the learning does not use Skinner's learning theory but through the Picture and Picture model. Of the total 36 students, there were 29 students who experienced an increase, so that the student's response after using Skinner's learning theory through the Picture and Picture model was considered good